Ectopic Pregnancy after Conservative Management of Placenta Accreta: A Case Report - Chun-Kuang Yang; Hsiao-Lin Hwa; Jin-Chung Shih; Fon-Jou Hsieh (Elsevier, 2004)
Objective: Placenta accreta can be managed with preservation of the uterus, especially when further fertility is intended. We report a case of placenta accreta diagnosed intraoperatively and treated conservatively that was followed by an ectopic pregnancy. Case Report: A 32-year-old woman was found to have placenta accreta during cesarean section. Some pieces of the placenta were left in situ after bleeding was controlled. The patient was followed up using levels of !-human chorionic gonadotropin. Hysteroscopy revealed fibrotic and scar tissue at the site of retained placenta 1 year later. The patient did not conceive until 2 years later, but it was an ectopic pregnancy. Conclusion: There are few reports of successful pregnancy following conservative treatment for placenta accreta. Conservative treatment may increase the risk of secondary infertility, recurrent placenta accreta, and probably ectopic pregnancy.